Investigation of the Required Earthquake Gap Distance between Reinforced Concrete Buildings with Nonlinear Time History Analysis - Cakil, Burak; Ince, Ozan; Atar, Muhammed; Ince, Elif Gokce (Afet ve Acil Durum Yonetimi Baskanligi (AFAD), 2025)
Earthquakes are caused by movements of the Earth's crust, resulting in destructive impacts on structures. One of the factors that increase the destructiveness of earthquakes is the pounding effect between buildings. Reinforced concrete buildings need to displace freely during seismic events. However, when the gap between adjacent buildings is insufficient, collisions occur, causing significant structural damage. This phenomenon, known as the pounding effect, can lead to severe damage during earthquakes. In this study, nonlinear time history analyses were conducted for two types of reinforced concrete buildings, 5-storey and 10-storey structures, to obtain their maximum displacement values. The minimum separation distances required to prevent pounding when these buildings are constructed adjacently were calculated and compared with the values specified in the 2018 Turkish Building Earthquake Code (TBEC-2018). The analysis results revealed that the distances calculated according to TBEC-2018 are insufficient. © (2025), (Afet ve Acil Durum Yonetimi Baskanligi (AFAD)). All rights reserved.
Betonarme Binalar Arasında Bırakılması Gereken Derz Mesafesinin Doğrusal Olmayan Zaman Tanım Alanında Analizler ile İncelenmesi
Keywords: Betonarme binalar; Derz mesafesi; Earthquake gap distance; Pounding effect; Reinforced concrete buildings; Structural damage; TBDY-2018; TBEC-2018; Yapı hasarı; Çekiçleme etkisi